HUBUNGAN PROFESIONALISME DOSEN DENGAN PRESTASI BELAJAR MAHASISWA S1 KEPERAWATAN DALAM MATA KULIAH KDM DI STIKES FLORA - Suherni, Suherni (Jurnal Keperawatan Priority, 2018)
A professional instructor is a person who has competence in carrying out educational and teaching tasks. He is expected not only to do his profession but also to have a calling to do his task by improving his service quality intellectually and the other professional competences which will support the learning-teaching activity and yield good performance for his students. Some instructors who teach the subject of KDM are still undergraduates who, according to PP RI No. 12/2012, are not professional instructors. The objective of this research was to find out the correlation of instructors’ professionalism with learning performance of S1 (Undergraduate) students in the subject of KDM at STIKes Flora, Medan. The research used descriptive correlation method with cross sectional design. It was conducted from April until June, 2015. The population was 37 S1 (Undergraduate) active students in the academic year of 2012-2013 who studied the subject of KDM, and all of them were used as the samples, using non-probability sampling or census sampling technique. Independent variable was instructors’ professionalism and dependent variable was learning performance. The data were gathered by distributing questionnaires and KDM Grade sheet. The statistic test consisted of univariate and bivariate analyses, distribution frequency and Spearman Rho correlation test. The result of the research showed that there was the correlation of instructors’ professionalism with learning performance of S1 (Undergraduate) students in the subject of KDM at 0.509 with p-value < α (0.001 < 0.05) at the significance level of 5%. It is recommended that all instructors of STIKes Flora, Medan, do their job professionally in order to achieve optimal and maximal educational service to increase students’ performance in the subject of KDM.